Democratic Republic of Timor Leste : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
The financial system of Timor-Leste was disrupted by the postreferrendum turmoil. Therefore, various steps were taken to restore the financial system. In this paper, major oil/gas fields and their development, fiscal arrangements governing oil/gas activities, and the oil/gas revenues are discussed. Fiscal and quasi-fiscal operations in Timor-Leste are governed by the central government, nonfinancial autonomous agencies, multilateral institutions, and bilateral donors. This study also summarizes statistical data of economic indicators, GDP by sectoral origin and by expenditure, consumer price index, monetary survey, oil/gas revenues, tax system, and so on.